Transformasi Lanskap dan Layanan Ekosistem Budaya di Area Peri-Urban: Wisata Alam dan Permukiman di Bandung Selatan - Medria Shekar Rani (Department of Urban and Regional Planning, Diponegoro University, 2021)
Peri-urban provides complementary urban ecosystem services when green areas in cities are decreasing due to densification. However, land cover change in the area from natural landscapes to agriculture and settlements affects the ecosystem's capacity to provide services. This study aims to identify landscape transformation using a model and analyze its effects on cultural ecosystem services at Kawah Putih (White Crater) nature-based tourism destination area in the peri-urban in South Bandung, Indonesia. This study also analyzes how cultural ecosystem services and the increasing demand for new settlements in the area have influenced tourist visitation. Landscape change in the area (1989-2019) was identified from mapsdeveloped from Landsat imagery, using the Land Change Modeler (LCM) module in Terrset. A spatial assessment of offered cultural ecosystem services was then conducted using three indicators based on the land cover change near Kawah Putih. It is found that the composition of developed areas in the district has increased from 6.09% to 10.79% in 30 years. The quality of cultural ecosystem service has decreased, which is arguably influenced by the landscape alteration in the area. However, there was an increasing trend in the number of tourists (2016-2019) despite the deterioration of landscape quality. It is argued that the result is influenced by the visitors' perception of the landscape in the case study area. The rapid land cover change in the area was affected by the nearby city's growth, in which the tourism industry is one of the elements of such transformation.